2009
DOI: 10.1111/j.1471-4159.2009.06415.x
|View full text |Cite
|
Sign up to set email alerts
|

The microtubule interacting drug candidate NAP protects against kainic acid toxicity in a rat model of epilepsy

Abstract: NAP (NAPVSIPQ, generic name, davunetide), a neuroprotective peptide in clinical development for neuroprotection against Alzheimer’s disease and other neurodegenerative indications, has been recently shown to provide protection against kainic acid excitotoxicity in hippocampal neuronal cultures. In vivo, kainic acid toxicity models status epilepticus that is associated with hippocampal cell death. Kainic acid toxicity has been previously suggested to involve the microtubule cytoskeleton and NAP is a microtubule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…Thus, NP031112 prevents inflammation and neurodegeneration under excitotoxic conditions [154], similar to davunetide [155].…”
Section: Recent Historic Perspectivementioning
confidence: 96%
“…Thus, NP031112 prevents inflammation and neurodegeneration under excitotoxic conditions [154], similar to davunetide [155].…”
Section: Recent Historic Perspectivementioning
confidence: 96%
“…For further reference on ADNP and NAP, please refer to our previous reviews with some examples cited here, [18,[45][46][47][48][49][50] and to our recent studies extending ADNP biology and NAP efficacy to other neurotrophic and neurodegenerative disease models [50][51][52][53][54][55][56][57][58][59][60].…”
Section: Introductionmentioning
confidence: 98%
“…An early study demonstrated the protective role of microtubule stabilization with taxol on hippocampal neurons exposed to kainic acid, [42]. Similarly the microtubule stabilizing agent davunetide protects against kainic acid excitotoxicity in hippocampal cells both in vitro and in vivo [43]. However in these studies taxol was globally applied to neurons and protection attributed to prevention of calcium influx through calcium permeable AMPA receptors [42].…”
Section: Discussionmentioning
confidence: 99%